The Role of School Principal Leadership on Committee Member Participation and Teacher Performance: Systematic Literature Review - Hariyono, Eko; Burhanuddin, Burhanuddin; Mustiningsih, Mustiningsih (Research, Training and Philanthropy Institution Natural Aceh, 2025)
This study aims to evaluate the influence of school principals' leadership on the participation level of school committee members and teacher performance. The research focuses on how leadership roles contribute to effective school management and the overall improvement of teaching quality. A Systematic Literature Review (SLR) was conducted by analyzing 42 journal articles published between 2014 and 2025. The review process involved identifying relevant studies, classifying key findings, and synthesizing evidence to draw comprehensive conclusions that reflect the educational context. The results indicate that principals' leadership has a positive impact on the active involvement of school committees, particularly through effective communication, participatory decision-making, and continuous empowerment. In addition, transformational leadership demonstrated by principals fosters a supportive and conducive school environment, enhances professionalism, and improves teacher performance. The findings confirm a strong positive correlation between school leadership, committee participation, and teacher performance. The implication of this study highlights the need to strengthen collaborative and transformational leadership practices to support teachers' professional growth, promote effective school governance, and ultimately improve the overall quality of education.